ANALISIS PRO-POOR GROWTH TINGKAT KABUPATEN/KOTA DI PROVINSI SUMATERA SELATAN, 2005-2011 (PENDEKATAN DIMENSI INCOME DAN NON-INCOME) - , Yoyok Cahyo Nugroho ([Yogyakarta] : Universitas Gadjah Mada, 2013)
The purpose of this study was to analyze pro-poor growth in the district/city of South Sumatra Province using the income and non-income dimensions approach in relation to the poverty rate changes since the early implementation of triple track strategy, from 2005 to 2011. This study is expected to know: (1) how the poverty condition and its change in terms of income and non-income dimensions, (2) how the growth effects and the distribution effects towards poverty changes, and (3) how the pro-poor growth level of the district/city in terms of income and non-income dimensions in South Sumatra Province. The concept of pro-poor growth is based on the idea that economic growth should benefit all parties, including the poor. Shapley Decomposition Technique is used to determine how the growth effects and the distribution effects towards the poverty changes in terms of those two dimensions. The pro-poor growth concept used in this study refers to Kakwani and Sonâs research (2008) which uses Poverty Equivalent Growth Rate (PEGR) method as a measure in determining the pattern of growth as pro-poor or anti-poor from the income dimension, as well as Grosse, Harttgen, and Klasenâs research (2008) which uses PEGR of non-income dimension. Using Susenas data of South Sumatra Province in 2005-2011, discover a tendency of non-income poverty rate higher than income poverty rate especially in rural areas dominated. Shapley decomposition shows trade-off between growth effects and redistribution effects against poverty changes. Growth which should be reducing the poverty level is often hampered by the redistribution effects that showed worsening inequality that accompanies growth. The trade-off is seen more clearly in the non-income dimensions which showed that educational development is still bias at population that has a secondary education and above. The calculation results of the pro-poor growth level by PEGR discovered that income growth tends to be trickle-down, although the poverty rate declines but the benefits of growth received by the poor proportionately less than the nonpoor. Income growth shows pro-poor in period of economic contraction, in which income redistribution programs such as BLT implemented nationally. Quadrant analysis results indicate that the pro-poor growth conditions worsened post-period 2008-2009 which characterized by most districts/cities are anti-poor growth of the two dimensions.